Effects and mechanisms of mindfulness training and physical exercise on cognition, emotional wellbeing, and brain outcomes in chronic stroke patients: Study protocol of the MindFit project randomized controlled trial - Bermudo-Gallaguet, Adrià; Ariza, Mar; Dacosta-Aguayo, Rosalia; Agudelo, Daniela; Camins-Vila, Neus; Boldó, Maria; Carrera, Òscar; Vidal, Sandra; Ferrer-Uris, Blai; Busquets, Albert; Via, Marc; Pera, Guillem; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Post-stroke cognitive and emotional complications are frequent in the chronic stages of stroke and have important implications for the functionality and quality of life of those affected and their caregivers. Strategies such as mindfulness meditation, physical exercise, or computerized cognitive training may benefit stroke patients by impacting neuroplasticity and brain health. Materials and Methods: One hundred and forty-one chronic stroke patients were randomly allocated to receive mindfulness-based stress reduction + computerized cognitive training (n = 47), multicomponent physical exercise program + computerized cognitive training (n = 47), or computerized cognitive training alone (n = 47). Interventions consisted of 12-week home-based programs five days per week. Before and after the interventions, we collected data from cognitive, psychological, and physical tests, blood and stool samples, and structural and functional brain scans. Results: The effects of the interventions on cognitive and emotional outcomes will be described in intention-to-treat and per-protocol analyses. We will also explore potential mediators and moderators, such as genetic, molecular, brain, demographic, and clinical factors in our per-protocol sample. Discussion: The MindFit Project is a randomized clinical trial that aims to assess the impact of mindfulness and physical exercise combined with computerized cognitive training on chronic stroke patients' cognitive and emotional wellbeing. Furthermore, our design takes a multimodal biopsychosocial approach that will generate new knowledge at multiple levels of evidence, from molecular bases to behavioral changes. Clinical Trial Registration: www.ClinicalTrials.gov, NCT04759950